Multidomain Response Patterns Following Focused Extracorporeal Shockwave Therapy in Diabetic Adhesive Capsulitis: A Secondary Analysis of a Randomized Controlled Trial - Siddharth Rai; Mallikarjun Gunjiganvi; Rupali Awale; Suruchi (Annals of Rehabilitation Medicine, 2026)
Objective: To characterize multidomain response patterns following focused extracorporeal shockwave therapy (fESWT) in patients with diabetic adhesive capsulitis across pain, functional, and mobility domains.Methods: This secondary exploratory analysis included 100 patients with type 2 diabetes mellitus and adhesive capsulitis who received active fESWT in a randomized controlled trial and completed 4-week follow-up. Clinically meaningful improvement was defined as a ≥2-point reduction in Visual Analogue Scale score, a ≥13-point improvement in Shoulder Pain and Disability Index score, and a ≥10° increase in active external rotation. Participants were classified according to combinations of domain-specific responses.Results: Global response, defined as concurrent improvement in pain, function, and mobility, was observed in 52.0% of patients. An additional 34.0% demonstrated improvement in pain and function without corresponding gains in external rotation, while 12.0% were classified as minimal or non-responders. Other discordant response patterns were uncommon (2.0%). Domain-specific response rates were 86.0% for pain, 88.0% for function, and 53.0% for external rotation, indicating that symptomatic and functional improvements occurred more frequently than recovery of shoulder mobility.Conclusion: Short-term response to fESWT in diabetic adhesive capsulitis demonstrates variable concordance across pain, functional, and mobility domains. Recognition of these multidomain response patterns may assist clinicians in interpreting early treatment effects and guiding rehabilitation planning.